Consumer valuation of Fintech: The case of Mobile Payment in Korea - Jinkyung Ha (International Telecommunications Society (ITS), 2018)
Fintech, the convergence of finance and internet related technology, is regard as new promising financial service. Among Fintech services, mobile payment which is new type of payment tool for consumer with smartphone started to draw attention. As the mobile payment started to replace current payment service, consumer valuation of the service is important as business viewpoint. In the case of valuation, totally four important attributes (origin, availability, economic benefit, and accessibility) were postulated for consumer decision making of mobile payment. This study conducted conjoint analysis to define ideal pair of mobile payment attributes. Result showed that among the four attributes, availability which refers to where the service can be used was mostly valued from consumers. This result corresponded to both user and non-user of mobile payment.
Keywords: 330